Digitisation of the Catalan Wine Sector: Analysis of the Online Communication of The Do Priorat, Empordà and Alella - Mundet, Jordi; Bustos Diaz, Javier; Mollevi Bortolo, Gemma (Transformations In Business & Economics, 2024)
Digitalisation plays an important role in today’s economy. Companies are beginning to understand that the Internet is the place where they need to be seen. For this reason, this work aims to analyze the online communication of the names of the place of origin of the winemakers Priorat, Empordà and Alella. To achieve this objective, a quantitative methodology is applied, and in particular, an analysis of the content of the websites of the winemakers in question is carried out and it is determined how the companies have adapted to the new technologies and the digital environment 2.0. in order to sell their brand and reach a larger audience. Thus, the main conclusion of this work is the need to update the digital image of these winemakers and to improve the way in which information is transmitted by modernising communication channels.